Extreme ion irradiation of oxide nanoceramics: Influence of the irradiation spectrum. (15th January 2018) - García Ferré, F.; Mairov, A.; Vanazzi, M.; Serruys, Y.; Leprêtre, F.; Beck, L.; Van Brutzel, L.; Chartier, A.; Beghi, M.G.; Sridharan, K.; Di Fonzo, F.
Abstract: Oxide nanoceramics combine the enhanced radiation tolerance of nanocrystalline materials with the chemical inertness of oxides, and are promising materials for highly corrosive and intense radiation environments. In this work, nanocrystalline Al2 O3 thin films are irradiated at 600 °C with either 12 MeV Au 5+ +18 MeV W 8+ or 4 MeV Ni 2+ ions. The radiation damage exposure exceeds 450 displacements per atom. A comprehensive analysis of the irradiated samples is accomplished by X-Ray Diffractometry (XRD), Transmission Electron Microscopy (TEM) and Scanning-TEM (STEM). Results are compared in an effort to establish correlations between the irradiation spectrum and the response of this class of materials to radiation environments. The results show that grain growth is the main microstructural change induced by ion irradiation in the material, regardless of the ion utilized in this work. The phase evolution may be depth-dependent, and depends strongly on the ion utilized and on the irradiation spectrum. 12 MeV Au 5+ +18 MeV W 8+ irradiations favor the formation of γ-Al2 O3 and α-Al2 O3, while 4 MeV Ni 2+ irradiations yield mainly δ-Al2 O3, accompanied by small α-Al2 O3 centers. Molecular dynamics simulations of displacement cascades are used to support discussions on the mass effect brought about by the different ions. Graphical abstract: Image